Napaść zbrojna w prawie międzynarodowym - w poszukiwaniu współczesnej definicji: [Armed attack in international law - in search of contemporary definition] (Studia Prawnicze / The Legal Studies, 2008)
Szeroko pojęta problematyka dopuszczalności użycia siły zbrojnej w prawie międzynarodowym publicznym zawsze należała do kwestii fundamentalnych. Jednakże w kilkunastu ostatnich latach stała się jeszcze bardziej aktualna i wymagająca pogłębionej refleksji. Związane jest to z pojawieniem się dwóch nowych uwarunkowań o podstawowym znaczeniu. Po pierwsze, począwszy od przełomu lat 80. i 90. XX w. doszło do gruntownej przemiany kształtu społeczności międzynarodowej, co musiało skutkować zapoczątkowaniem istotnych zmian w samym prawie międzynarodowym, które jest przecież niczym innym niż instrumentem regulacji stosunków w tej społeczności. Po drugie, na niespotykaną dotychczas skalę wzrosło zagrożenie przybierającym nowe formy terroryzmem międzynarodowym- symbolem pozostaje tu oczywiście 11 września 2001 r. i rozpoczęta następnie tzw. wojna z terroryzmem. The text analyses one of the key notions of Chapter VII of the United Nations Charter, namely the armed attack notion. The interpretation of this notion-which still misses the generally accepted definition-is of crucial significance as it de termines the scope of the right to self-defence under Article 51 of the UN Charter, which together with the collective security system create the only two exceptions to the prohibition on the use of armed force in international law. The notion is interpreted in relation to the use of force notion and the act of aggression notion. The understanding of the armed attack notion as the gravest form of the use of force is challenged. Also, the problem of the source of an armed attack is ana lysed. It is submitted that non-state actors themselves may not be perceived as a source of an armed attack. However, the standards relating to the attribution of non-state actors' military actions to states should be extended. In general, the pre sented interpretative approach towards defining the armed attack notion shows that it is indeed possible to interpret the jus ad bellum norms in such a manner as to, on the one hand, carefully adjust them to new threats in order to let states respond individually more adequately, but, on the other hand, to remain within the framework of the UN Charter and keep all the system safeguards.